Genome-Wide Identification and Evolutionary Analysis of AOMT Gene Family in Pomegranate (Punica granatum) - Xinhui Zhang; Weicheng Yuan; Yujie Zhao; Yuan Ren; Xueqing Zhao; Zhaohe Yuan (Agronomy, 2021)
Gene duplication is the major resource with which to generate new genes, which provide raw material for novel functions evolution. Thus, to elucidate the gene family evolution after duplication events is of vital importance. Anthocyanin O-methyltransferases (AOMTs) have been recognized as being capable of anthocyanin methylation, which increases anthocyanin diversity and stability and improves the protection of plants from environmental stress. Meanwhile, no detailed identification or genome-wide analysis of the AOMT gene family members in pomegranate (Punicagranatum) have been reported. Three published pomegranate genome sequences offer substantial resources with which to explore gene evolution based on the whole genome. Altogether, 58 identified OMTs from pomegranate and five other species were divided into the AOMT group and the OMT group, according to their phylogenetic tree and AOMTs derived from OMTs. AOMTs in the same subclade have a similar gene structure and protein conserved motifs. The PgAOMT family evolved and expanded primarily via whole-genome duplication (WGD) and tandem duplication. PgAOMTs expression pattern in peel and aril development by qRT-PCR verification indicated that PgAOMTs had tissue-specific patterns. The main fates of AOMTs were neo- or non-functionalization after duplication events. High expression genes of PgOMT04 and PgOMT09 were speculated to contribute to “Taishanhong” pomegranate’s bright red peel color. Finally, we integrated the above analysis in order to infer the evolutionary scenario of AOMT family.